Peran Mahasiswa Kampus Mengajar dalam Meningkatkan Minat Olahraga Siswa di Sekolah Dasar Negeri 01 Abung Jayo - Khoriyah, Dwi Darojatun; Sumarno, Sumarno (Publikasi Pendidikan, 2025)
The Kampus Mengajar students play an active role in introducing various types of sports to students, including pencak silat, gymnastics, and team games, using a creative and enjoyable approach. This study aims to explore the role of Kampus Mengajar students in increasing students' interest in sports at SD Negeri 01 Abung Jayo. The method used is descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. The results of the study show that Kampus Mengajar students successfully created an engaging and enjoyable atmosphere in sports activities, which increased student participation. In addition, sports activities also provide benefits in the development of social skills, such as teamwork and discipline. Despite challenges related to limited sports facilities, the presence of Kampus Mengajar students has had a positive impact on sparking students' interest in sports. This study suggests improving sports facilities at the school and further support from various parties to ensure the sustainability of this program.